1961. A Randomized Controlled Trial of the Effect of Accelerated Copper Textiles on Healthcare-Associated Infections and Multidrug-Resistant Organisms: The "Investigating Microbial Pathogen Activity of Copper Textiles" (IMPACT) Study. (26th November 2018) - Lautenbach, Ebbing; Pegues, David; Fuchs, Barry; Martin, Niels; Nachamkin, Irving; Bilker, Warren; Tolomeo, Pam; Cressman, Leigh; Omorgobe, Jacqueline; Johnson, Kristen; Han, Jennifer
Abstract: Background: Healthcare-associated infections (HAIs) and multidrug-resistant organisms (MDROs) remain critically important problems. Although copper has well-described antimicrobial properties, the impact of copper-impregnated linens on HAIs and MDROs in healthcare settings remains undefined. Methods: This study was conducted in a 24-bed medical ICU and a 24-bed surgical ICU from 1/12/16 to 7/31/16. Six beds in each ICU were randomized to CottonX™ accelerated copper linens (flat sheet, fitted sheet, pillow cover, gown) (Argaman Technologies Ltd.) and 18 beds to regular linens. Patients were enrolled if they were in the ICU for ≥3 days and were followed prospectively for development of an HAI (including C. difficile infection) and/or MDRO from ICU day 3 through 2 days after ICU discharge. MDROs were defined as a new clinical culture (i.e., no culture with the same organism in the prior year) with methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, or ceftriaxone-resistant or carbapenem-resistant Enterobacteriaceae. A patient could be included more than once for distinct ICU stays ("episodes"). Results: Among 1, 021 subjects, the median age was 61 and 448 (44%) were female. Of 1, 205 total episodes, 678 (56%) were in the MICU, 527 (44%) were in the SICU, and 351 (29%) were randomized to copper rooms. There were no significant differences between study groups with regard to demographics, comorbidities, indwelling devices, or antibiotic use. The overall rate (per 1, 000 patient-days) of the composite outcome (HAI or MDRO) was 11.66 and 15.44 in copper and non-copper episodes, respectively, [incidence rate ratio (IRR) = 0.76 (95% CI, 0.46, 1.19); P = 0.22]. Rates of HAIs were 10.26 and 10.41 for copper and non-copper episodes, respectively ([IRR (95% CI) = 0.99 (0.57, 1.64); P = 0.97]. Rates of MDROs were 3.73 and 6.51 for copper and non-copper episodes, respectively [IRR (95% CI) = 0.57 (0.23, 1.26); P = 0.15]. Results were consistent when stratified by type of ICU. Conclusion: While not statistically significant, there was a nearly 50% lower rate of MDRO infection and colonization with use of CottonX™ accelerated copper linens, possibly in part due to decreases in environmental contamination. Future work should further explore the role of copper linens in reducing MDROs. Disclosures: D. Pegues, DaVita / Total Renal Care: Consultant, Consulting fee.